Markeninszenierung in Japan: Zur narrativen Konstruktion der Lifestyle-Marken »Muji« und »Uniqlo« - Rühle, Christiane (transcript, 2020)
The image building of internationally successful lifestyle brands of Japan is examined from an interdisciplinary perspective: actors, structures and practice of brand staging.